Working alongside Robotic Process Automation and emergence of technostress - Haapanen, Kimmo (2024)
Two phenomena are increasingly common: the increased use of technology in working life and the increase in sickness absences due to mental health problems and stress in the working age population. While the two could be linked only coincidentally, technostress is an existing burden for many people who are in contact with technology in an occupational context. The ways of working and the continuity of work roles are under constant pressure of change. One force for change is the increased use of automation at organizations. One such area of automation is the use of Robotic Process Automation (RPA). RPA is set to promise an increase in efficiency and reduction in repetitive tasks at work. With RPA the desired effect is on the positive side, but at the same time knowledge about the negative side is light or non-existent in the academic literature. Technostress has many effects on workers in organizations which may lead to symptoms like emotional outbursts, negative moods and conflicts. This study aims to increase understanding of the human interaction with RPA as a technology, experiences of technostress and occupational stress at the workplace and how they interact with each other. The technology of RPA and the interaction between technostress and occupational stress are both understudied as of now. The data was gathered through qualitative interviews of 22 experts working alongside RPA either as end users or as technical stakeholders responsible for upkeep of the technology from multiple organizations and roles. The results suggest that technostress exists in the field of RPA as well, but it also interacts with occupational stress through workflow disruptions and performance hindrances, which increases the overall stress load of an individual. The use of technology also makes teams more susceptible to experience of stress through rustification of skills needed to conduct the automated tasks in cases of RPA malfunction, and also by making working days more intense. The RPA also causes different kinds of stress experience in different stages of the RPA lifecycle. Lastly RPA causes different kinds of stress experience depending on your viewpoint as an end user or as a technical person. These results provide novel understanding on how RPA causes a mix of technostress and occupational stress and how the maturity of the RPA and the viewpoint of the individual modify the stress experience.